Effect of food on the pharmacokinetic characteristics of a single oral dose of LCB01-0371, a novel oxazolidinone antibiotic - Sunwoo J; Kim YK; Choi Y; Yu KS; Nam H; Cho YL; Yoon S; Chung JY (Dove Medical Press, 2018)
Jung Sunwoo,1 Yu Kyong Kim,1 Yewon Choi,1 Kyung-Sang Yu,1 Heesook Nam,2 Young Lag Cho,2 Seonghae Yoon,3 Jae-Yong Chung3 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, 2LegoChem Biosciences, Inc., Daejeon, 3Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Bundang Hospital, Seongnam, Republic of Korea Background: LCB01-0371 is a novel oxazolidinone antibiotic that blocks protein production by binding to bacterial 23S ribosomes. This antibiotic is active against Gram-positive bacteria. This study aimed to evaluate the effect of food on the pharmacokinetics (PKs) of LCB01-0371 and evaluate its safety profile.Subjects and methods: A randomized, open-label, two-way crossover study was performed in 18 healthy Korean male subjects. All subjects received a single oral 800 mg dose of LCB01-0371 in each period under fed or fasting condition with a 7-day washout in between. The fed condition was defined as consumption of a meal of 800–1,000 kcal containing ~50% of fat content. Serial blood samples were collected over 24 h after dosing, and the PK parameters were calculated by noncompartment analysis. All available data of the subjects who received LCB01-0371 at least once were included in the safety data summaries.Results: In the fed condition, both the maximum plasma concentration (Cmax) and the total systemic exposure (area under the plasma concentration–time curve from time zero to the last observed time point [AUClast]) decreased by ~33% and 10%, respectively. The time to reach Cmax was delayed by ~1.25 h in the fed condition, whereas the mean elimination half-life remained similar in both conditions. In the fed/fasting condition, the geometric mean ratios and 90% CI of the Cmax and AUClast were 0.666 (0.470–0.945) and 0.897 (0.761–1.057), respectively. There were no drug-related adverse events (AEs) or serious AEs.Conclusion: Although the Tmax after a single oral 800 mg dose of LCB01-0371 was slightly delayed under the fed condition compared to the fasting condition, the total systemic exposure was similar under both conditions. Therefore, LCB01-0371 could be administered regardless of food intake. Keywords: antibiotic resistance, gram-positive bacteria, clinical trial